Faktor-Faktor Yang Mempengaruhi Produktivitas (Studi Pada Karyawan Bagian Produksi PT Nusantara Building Industries) - ., Supriyanto; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The purpose of this study was to find out the influence of theknowledge, skills, abilities, attitudes and behaviors on the productivity of the employeesof the production department of PT Nusantara Building Industries. The population in thisstudy was 483 employees of the production department of PT Nusantara BuildingIndustries. While the samples were 83 respondents. The sampling techniques used wasnon probability sampling with convenience. The analysis tool used in this research wasmultiple linear regression, which was firstly examined by validity and reliability test. Theresults showed partially, it obtained by value for X1 = 3.800; X2 = 2.511; X3 = 2.216; X4= 2.188, and X5 = 3.945 while t table 1.991 that was in the area reject Ho, meaning therewas significant influence of between the knowledge, skills, abilities, attitudes andbehaviors on the productivity of the employees of the production department of PTNusantara Building Industries. While the hypothesis test simultaneously with the testresults obtained F value = 28.757> F table = 2.333 was in the reject Ho area, meaningthat there was significant influence of knowledge, skills, abilities, attitudes and behaviorson the productivity of the employees of the production department of PT NusantaraBuilding Industries. The coefficient of determination of the five independent variables =62.9% meaning that the variation of the five independent variables in explainingproductivity = 62.9% while the remaining 37.1% was explained by other variables thatwere not mentioned in this study.Keywords: productivity, knowledge, skills, abilities, attitudes, and behaviors